Lingkungan kerja, Disiplin kerja, Beban kerja terhadap Produktivitas karyawan PT. Aneka Rupa - Ilhami, Putri; Firdaus, Vera; Andriani, Dewi (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the influence of the work environment, work discipline, workload on employee productivity at PT Aneka Rupa. This research uses quantitative methods with a descriptive approach. This research uses data collection techniques through questionnaires processed using PLS (Partial Least Square). In this research, total sampling technique was used. The research population was employees of PT Aneka Rupa with a total of 100 employees, with analysis techniques using multiple linear regression analysis. The research results show that the work environment and work discipline have an influence on productivity. Meanwhile, workload has no effect on the productivity of PT Aneka Rupa employees.